A facile freeze–thaw ultrasonic assisted circulation method of graphite flakes prepared by anode graphite from spent lithium-ion batteries for application in nanofluids. Issue 19 (2nd September 2021) - Qiao, Yu; Sheng, Wen; He, Chen; Yang, Bai; Xu, Haoxuan; Liu, Chenzhen; Rao, Zhonghao
Abstract : A facile freeze–thaw ultrasonic assisted circulation method to prepare two-dimensional low-layers graphite by anode graphite from spent LIBs was proposed. Abstract : Graphite has been widely used as the anode material in lithium-ion batteries (LIBs) due to its good conductivity, layered crystal structure, high charging–discharge potential, and other characteristics. With the rapid development of the LIB industry, the graphite industry has also developed into a mode of high production capacity. The anode graphite of spent LIBs has the characteristics of large layer spacing and ease of being intercalated and peeled due to the reduction of the interlamination force after repeated charge and discharge cycles. In this study, we present a facile freeze–thaw ultrasonic assisted circulation method to prepare two-dimensional low-layer graphite flakes (GFs) using anode graphite from spent LIBs. Characterizations of GFs were carried out by SEM, TEM, XRD and Raman spectroscopy. The results indicate that GFs prepared by graphite of spent LIBs have a better morphology than that prepared by purchased graphite. Furthermore, the GF-filled ethylene glycol (EG) nanofluids exhibit higher thermal conductivity and conductive heat transfer coefficient than base fluids, of which the maximum enhancements are 10.5% and 30%, respectively. The freeze–thaw ultrasonic assisted circulation method is not only an effective method for the reuse of anode graphite from spent LIBs, but also a reference for the synthesis of two-dimensional materials. Furthermore, GF-filled nanofluids could be a potential heat transfer working medium.